Metabolomics Provides New Insights into the Mechanisms of Wolbachia-Induced Plant Defense in Cotton Mites - Xinlei Wang; Sha Wang; Ali Basit; Qianchen Wei; Kedi Zhao; Feng Liu; Yiying Zhao (Microorganisms)
Endosymbiotic bacteria play a significant role in the co-evolution of insects and plants. However, whether they induce or inhibit host plant defense responses remains unclear. In this study, non-targeted metabolomic sequencing was performed on cotton leaves fed with Wolbachia-infected and uninfected spider mites using parthenogenetic backcrossing and antibiotic treatment methods. A total of 55 differential metabolites were identified, which involved lipids, phenylpropanoids, and polyketides. KEGG pathway enrichment analysis revealed seven significantly enriched metabolic pathways. Among them, flavonoid and flavonol biosynthesis, glycerophospholipid metabolism, and ether lipid metabolism showed extremely significant differences. In Wolbachia-infected cotton leaves, the flavonoid biosynthesis pathway was significantly up-regulated, including quercetin and myricetin, suggesting that the plant produces more secondary metabolites to enhance its defense capability. Glycerophosphocholine (GPC) and sn-glycerol-3-phosphoethanolamine (PE) were significantly down-regulated, suggesting that Wolbachia may impair the integrity and function of plant cell membranes. The downregulation of lysine and the upregulation of L-malic acid indicated that Wolbachia infection may shorten the lifespan of spider mites. At various developmental stages of the spider mites, Wolbachia infection increased the expression of detoxification metabolism-related genes, including gene families such as cytochrome P450, glutathione S-transferase, carboxylesterase, and ABC transporters, thereby enhancing the detoxification capability of the host spider mites. This study provides a theoretical basis for further elucidating the mechanisms by which endosymbiotic bacteria induce plant defense responses and expands the theoretical framework of insect–plant co-evolution.